Higher education volume and value of output: experimental calculations for Malaysia - Khalid, Haniza (Educational Management, Planning & Policy, Faculty of Education, University of Malaya, 2016)
The valuation of higher education’s contribution to the national economy in the past has typically been based upon costs of inputs. However, such an approach neglects any productivity or quality variations in the outputs of higher education, mainly from teaching services and research. An increasing number of countries are now using output-based measures of the volume of higher education services. This paper describes a quantitative approach for output-based measurements using publicly available data in order to attempt a preliminary application for Malaysia. Government’s development and operational budget on education and training increased significantly after 2007 with the implementation of the National Higher Education Strategic Plan (NHESP). Using the output approach, we find that value of teaching services by the public HE sector rose by 5.2 per cent that from RM13.77 billion to RM14.48 billion in 2010 although aggregate enrolment grew by 9.9 per cent; as compared to 5.1 per cent increase in operational budget for the same period. The result is justified given that higher percentage of the new enrolments are often found in advanced levels of study (postgraduate courses) which cost less per unit of quantity – as there is less coursework involved. The finding sheds light on the nature of NHESP’s impact on national income and provides helpful inputs to future refinements of the national strategic plan.